ANALISIS KENAIKAN HARGA PROPERTI RESIDENSIAL SEDERHANA UNTUK WILAYAH KELURAHAN BELIAN - Usmanul Hayadi Umar; Rizki Dwi Putra (Journal of Civil Engineering and Planning (JCEP), 2020)
In the House Price Index (HPI), the Riau Islands Province (Riau Islands) is the province with the highest property price growth in Indonesia as of June 2018, the property price index in Riau Islands reaches 215.43 or up 20.09 percent compared to 2017. The increase was due to the development of the property industry in Batam. HPI in Riau Islands has an average growth of 20.09 percent driven by property developments in Batam which continue to increase. The method used is observation and survey. The method used uses multiple linear regression. The results of multiple linear regression testing using SPSS 21.0 Software. Test results obtained on the t test and from the interpretation of the model obtained Y = 30,758,000 + 479,000 (Area_Tanah) + 3,048,000 (Luas_Bangunan). Where, independent variables namely Land Area and Building Area are included in the regression model if the land area increases by 1 square meter, then the selling price of the house will increase by Rp 479,000.00 and if the building area increases by 1 square meter, the selling price of the house will increase by Rp. 3,048,000.00. Prediction of house selling price for land area of ​​72 m² and building area of ​​36 m² are: Y = βo + β1X1 + β2X2, Y = βo + β1Luas_Tanah + β2Luas_Bangunan, Y = Rp. 30,758,000 + Rp. 479,000 x 72 + Rp 3,048,000 x 36 , Y = Rp. 174,974,000. Description: Y = The Selling Price of the House to Be Marketed.